Microbial dynamics of antibiotic resistance.
Microbial antibiotic resistance develops in the gut through the selection of pre-existing resistant bacteria and gene transfer events. Scientists investigated the dynamics of the entire collection of 'Antimicrobial resistance determinants' (ARDs), also known as the resistome, in the human gut.